Structure of Human adenovirus 7 virus-like particles, a platform for developing nanotherapeutics and studying capsid assembly - Kiyano Madoo; Ryan Mazboudi; Zubaida Marufee Islam; Jonathan Luo; Robert A. Kuschner; Paul Gottlieb; John J. Dennehy; Rinat R. Abzalimov; Jose M. Galarza; Reza Khayat (Proceedings of the National Academy of Sciences, 2026)
Adenoviridae family members routinely infect humans, exhibit significant genetic diversity, and are associated with a variety of illnesses. Types 4 and 7 frequently circulate in the United States and are major causes of respiratory disease. Infections can result in hospitalization and, in severe cases, death. Although a live wild-type-virus vaccine targeting these two types exists, its use is restricted to military personnel due to concerns about viral-shedding and potential for genetic recombination. To overcome these limitations, we recently developed a virus-like particle (VLP) platform as an alternative vaccination strategy. These VLPs are stable, lack genomic material, and elicit a potent humoral immune response in mice, effectively neutralizing adenoviral infection. Here, we describe the cryo-EM structure of adenovirus 7 (AdV-7) VLPs. Structural insights are essential to ensure that neutralizing antigens displayed on the VLPs accurately mimic those of the virion, guide the design of particles with improved stability and efficacy, and enable engineering of VLPs with antigenic properties targeting multiple adenovirus types. The structure shows that hexon, penton, pIIIa, pVI, pVIII, and IX assemble comparable to AdV-5, hexon and penton neutralizing epitopes are appropriately displayed for antibody recognition, penton insertion into the hexon shell promotes cement protein pIIIa to increase its interaction with the peripentonal hexons, and presence of the core-genome is associated with increased interaction between cement protein pVIII and hexon. Finally, limited proteolysis and mass spectrometry demonstrate that VLP incorporated hexons digest more readily than virion incorporated hexons, indicating the greater dynamic nature of the VLP.